Understanding the perceived influence of social capital by homeless persons in Newton, Kansas - Limon, Lester Lloyd II (Kansas State University, 2014)
This is an exploratory study investigating: How those currently experiencing homelessness perceive the influence of bonding and bridging social capital on their future successful residential reintegration. It is an important consideration in understanding the emotional and intellectual circumstances of residents entering a rural shelter environment, and discovering what types of social capital residents need and have access to. This research used phenomonography to gain access to the thoughts and opinions of residents of the Harvey County Homeless Shelter, coupled with grounded theory to discover emergent themes in those transcripts. The study topic was explored through direct inquiry of people experiencing homelessness in Newton, Kansas. Through an interview process, five areas of inquiry were studied: demographics, residential history, social connections, community connections, and social connectedness and community belonging. Using grounded theory methodology, the responses were coded and the writing of rich memos determined and explored themes. Emergent themes; an analysis of their relevancy to the study topic; an examination of the areas the study topic satisfied; and, identification of areas where it failed to satisfy are topics of exploration concerning the findings. Community courtesy, individual personality, healthy relationships, and social connections over address were the four emergent themes to come from the five categories of inquiry. In general, resident’s perceptions of social capital were important to their future efforts toward residential reintegration, although in slightly different ways than the study topic assumed.
Keywords: Homelessness; Kansas; Social capital; Social Research (0344)